Tráfico e navios negreiros: contribuição da Arqueologia Náutica e Subaquática - Gilson Rambelli (Navigator)
The papers aims at contributing to producing a new approach, nautical and archaeological, on the maritime slave trade. It refers to a classic topic in international historiography, namely the African slave traffic to Brazil. It also aims at studying the wreck of a US slave ship, at Angra dos Reis, where it sunk in 1852. Through the study of material culture it will be possible to understand history as it is not written in history textbooks.